2014
DOI: 10.1186/1472-6963-14-122
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture in a large teaching hospital in Riyadh: baseline assessment, comparative analysis and opportunities for improvement

Abstract: BackgroundIn light of the immense attention given to patient safety, this paper details the findings of a baseline assessment of the patient safety culture in a large hospital in Riyadh and compares results with regional and international studies that utilized the Hospital Survey on Patient Safety Culture. This study also aims to explore the association between patient safety culture predictors and outcomes, considering respondent characteristics and facility size.MethodsThis cross sectional study adopted a cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
164
5
20

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(225 citation statements)
references
References 15 publications
36
164
5
20
Order By: Relevance
“…Like previous studies, all patient safety culture elements showed positive correlations with each other with one exception: there was no relationship between "frequency of events" and "management support," "teamwork within units," "teamwork across," "staffing, handoffs transitions" and "non-punitive responses" (29)(30)(31). similar to previous studies, "staffing" scored the lowest among all the patient safety culture elements (28) and "teamwork within units" (32,33) scored the highest in this study. Patient safety cultures within hospitals still require development.…”
Section: Discussionsupporting
confidence: 84%
“…Like previous studies, all patient safety culture elements showed positive correlations with each other with one exception: there was no relationship between "frequency of events" and "management support," "teamwork within units," "teamwork across," "staffing, handoffs transitions" and "non-punitive responses" (29)(30)(31). similar to previous studies, "staffing" scored the lowest among all the patient safety culture elements (28) and "teamwork within units" (32,33) scored the highest in this study. Patient safety cultures within hospitals still require development.…”
Section: Discussionsupporting
confidence: 84%
“…It reflects a fact that there is a significant lack in staffing and resource adequacy, poor nurse leadership, nurse physician relationship, additional physician related items, inadequate nursing foundation for quality of care and nurse participation in hospital affairs. These findings come in agreement with Alahmadi; El-Jardali et al, who reported that shortage of nursing staff leads to an increase in workload, and this pressure is considered a major cause of errors [25,26]. Furthermore, the nursing environment which include arrangement of nursing units, technological equipment, communication, knowledge transfer among staff, inadequate policies, fatigue, stress and workload are significant factors affecting patient safety and the quality of care [19,27,16,28].…”
Section: Discussionsupporting
confidence: 81%
“…30 A finding that might reflect the defective training and negligence of Beni-Suef HCWs of the importance of patient safety event reporting. As regard the correlation between frequency of events reporting and the 10 composites of patient safety, 9 dimensions showed positive correlation with frequency of events reporting strongest of which was observed for communication openness (r=0.362) while teamwork within hospital units showed the weakest correlation (r=0.185) ( 31 and teamwork across hospital units 26 , while the weakest correlation was for on supervisor manager expectations to promote patient safety (Pearson r = 0.081). 31 In addition, there was positive correlation between the dimension overall perception of safety and 9 dimensions of patient safety in the current study, strongest of which was for handoffs & transitions (r=0.531) while the weakest was that for management support for patient safety (r=0.142) ( Table 4).…”
Section: Discussionmentioning
confidence: 96%
“…As regard the correlation between frequency of events reporting and the 10 composites of patient safety, 9 dimensions showed positive correlation with frequency of events reporting strongest of which was observed for communication openness (r=0.362) while teamwork within hospital units showed the weakest correlation (r=0.185) ( 31 and teamwork across hospital units 26 , while the weakest correlation was for on supervisor manager expectations to promote patient safety (Pearson r = 0.081). 31 In addition, there was positive correlation between the dimension overall perception of safety and 9 dimensions of patient safety in the current study, strongest of which was for handoffs & transitions (r=0.531) while the weakest was that for management support for patient safety (r=0.142) ( Table 4). Findings are in agreement with Higher scores on hospital handoffs and transitions 26 and not in agreement with the reported strongest correlation for hospital management support for patient safety (Pearson r = 0.352) and weakest for non-punitive response to error (Pearson r = 0.176).…”
Section: Discussionmentioning
confidence: 96%